2009
DOI: 10.1111/j.1744-7909.2008.00804.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Contaminant Removal Effect of Several Plants in Constructed Wetlands

Abstract: The aim of the present study is to probe the relation between plant growth and its decontamination effect in constructed wetlands. Four species were studied in the small-scale mono-cultured constructed wetlands, which were fed with domestic wastewater. Plant growth indexes were correlated with contaminant removal performance of the constructed wetlands. Wetlands planted with Cyperus flabelliformis Rottb. showed the highest growth indexes such as shoot growth, biomass, root activity, root biomass increment, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 57 publications
(58 reference statements)
0
9
0
Order By: Relevance
“…(1.7 g plant −1 day −1 ) in the aerial portion of the plant, greater values were found in the experiment performed by Cheng et al (2009): 2.8 g plant −1 day −1 for C. flabelliformis and lower values, between 0.4 and 0.5 g plant −1 day −1 , for the species Acorus calamus, Phragmites australis and Vetiveria zizanioides, planted in horizontal CWs for treatment of domestic sewage under a load of 2.6 gm −2 day −1 of COD. Working with C. involucratus in vertical CWs for treating of synthetic wastewater (300 gm −3 of COD and 300 gm −3 of N T ) under an average load of 13.7 g m −2 day −1 of COD, Kantawanichkul et al (2009) observed a dry matter production rate of 28.7 g m −2 day −1 , greater than that observed for Cyperus sp.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…(1.7 g plant −1 day −1 ) in the aerial portion of the plant, greater values were found in the experiment performed by Cheng et al (2009): 2.8 g plant −1 day −1 for C. flabelliformis and lower values, between 0.4 and 0.5 g plant −1 day −1 , for the species Acorus calamus, Phragmites australis and Vetiveria zizanioides, planted in horizontal CWs for treatment of domestic sewage under a load of 2.6 gm −2 day −1 of COD. Working with C. involucratus in vertical CWs for treating of synthetic wastewater (300 gm −3 of COD and 300 gm −3 of N T ) under an average load of 13.7 g m −2 day −1 of COD, Kantawanichkul et al (2009) observed a dry matter production rate of 28.7 g m −2 day −1 , greater than that observed for Cyperus sp.…”
Section: Resultsmentioning
confidence: 58%
“…used in this experiment. Cheng et al (2009), under the previously mentioned conditions, observed that the greatest reductions in pollutants occurred in the CW planted with C. flabelliformis, and the same presented the greatest biomass production and the fastest growth rate. This confirms that the vegetation has a significant influence on removal of pollutants.…”
Section: Resultsmentioning
confidence: 86%
“…However, it remains unclear how these nutrient removal differences occur between plants with comparable size and growth form (Brisson & Chazarenc, 2009). Nutrient removal ability of wetland plants is reported to be correlated with biomass (Tanner, 1996), growth speed and growth rhythm (Cheng et al, 2009a), and root morphology and distribution (Sorrell et al, 2000;Lorenzena et al, 2001;Kyambadde et al, 2004;Amon et al, 2007;Cheng et al, 2009b). However, results are still very inconsistent and little generalization has been made to help guide species selection (Brisson & Chazarenc, 2009;Vymazal & Kröpfelová, 2009).…”
Section: Introductionmentioning
confidence: 94%
“…The roots were washed over a sieve and measured for fresh and dry weights. The root biomass increment was used as an estimate of root growth (Cheng et al, 2009a).…”
Section: Growth and Biomassmentioning
confidence: 99%
“…It is revealed that the plant root biomass was positively related to urease, acid, and alkaline PP activities [38]. This result might be to some extent related to the effect of the higher root respiration rate on the oxygen content in the rhizosphere, since Cheng et al concluded ammonia nitrogen removal was significantly related to the plant aboveground biomass and nitrogen removal highly correlated with the plant photosynthetic rate in micro-scale gravel-bed CWs [39]. In this study, some significant correlations were detected between plant parameters (biomass, root number, leaf number, and height) and enzyme activities (PP and UR) in DFC and UFC, and the maximum activities of NR, UR, and PP occurred during summer or autumn in DFC and UFC when plants were in the vigorous growth stage, which was consistent with a report of Kong et al, who found that many significant positive correlations between soil enzyme activity was positively related to root activity [32].…”
Section: Discussionmentioning
confidence: 95%